Silent sitting and study discipline of students at tri ratna elementary school in Jakarta - Gopin Gopin; Juni Suryanadi; Burmansah Burmansah (Universitas Sebelas Maret, 2025)
The purpose of this study is to determine the effect of silent sitting on improving the learning discipline of students at Tri Ratna Elementary School in Jakarta. The problems encountered by students include a lack of seriousness in following lessons, students who are busy with their own activities and do not listen to the teacher's explanations, students who like to run around during teaching and learning activities, students who arrive late at school, and students who like to leave and return to class during lesson time. This study uses a quantitative approach, with a survey method and data processing techniques based on the results of the instrument distribution. To determine the sample size for each class, a proportional allocation of 93 samples was used, consisting of 37 fourth-grade students, 24 fifth-grade students, and 32 sixth-grade students. This research was conducted at Tri Ratna Elementary School in Jakarta, with respondents from grades IV, V, and VI in the 2024/2025 academic year. The results showed that silent sitting had a strong and significant effect on improving learning discipline. This effect indicated that the more often silent sitting was practiced, the better the level of learning discipline that could be achieved. From the regression analysis, it was found that silent sitting played a major role in improving student learning discipline, although there were also other factors that had a smaller influence. These results indicate that silent sitting can be a major factor in creating learning discipline both at school and at home. In addition, there was an increase in students' concentration and self-control after regularly practicing silent sitting. This proves that mindfulness-based relaxation techniques are effective in gradually forming habits of discipline.